PENYELESAIAN SENGKETA INVESTASI MELALUI INTERNATIONAL CENTRE FOR SETTLEMENT OF INVESTMENT DISPUTE (Studi Kasus Pemerintah Indonesia vs Churchill Mining) - Geraldi, Aldo Rico (Faculty of Law, Tanjungpura University, 2017)
This research aims to determine International Centre For Settlement of Investment Dispute (ICSID), benefits and losses for Indonesia related with Choice of Option on Indonesian investment dispute settlement with Churchill Mining Plc in ICSID. This research uses normative legal research by gathering secondary data. Data collected is using the methods of literary study by collecting legal material and information in the form of legal materials of primary sources, secondary sources, and tertiary sources. In order to get a clear explanation, the data will arrange systematically and analyzed with descriptive methods. These results indicate that the disputes settlement between Indonesian Government against Churchill Mining through ICSID has several benefits, such as the confidentiality of the proceedings, the freedom to choose the arbitrator, the decision of the ICSID which are final and binding, and if the arbitration decision can be implemented in Indonesia it is necessary to obtain Exequatur of the Supreme Court. Although it has some benefits, however there are also some of the losses suffered by Indonesian Government, such as substantial costs to finance the proceedings at ICSID and if Indonesia was lost, it can cause financial loss with very large impact to country around trillions to pay compensation or indemnity.